CHALLENGES AND MANAGEMENT STRATEGIES OF SPECTATORS CROWD IN SELECTED STADIUMS, ETHIOPIA - B.F, Dawit; D. (Ph.D) , Wondemagegn; M., Mekoya (ETHIOPIAN JOURNAL OF SPORT SCIENCE, 2021)
The purpose of this study is to assess the challenges and management strategies of spectators’ crowd in selected stadiums, Ethiopia. Hawassa Kenema and Addis Ababa stadiums are selected for study site, whereas stadium safety feature, management strategies in terms of pre, during and post-event management activities and major hindering factors are the selected study variables. To achieve the innate objective 387 subjects are selected by multi stage sampling techniques from Spectators, volunteers, officers and executives. Cross sectional survey research design is employed to manipulate study variables. Apart from this adopted Simpson, 2000 questionnaire is administered to collect relevant information from study subject. The descriptive and Logistic regression statistical analysis using SPSS V 20 is employed to interpret the result. However level of significant is set at p <0.05. The statistical analysis reveals as the application of pre, during and post events management strategies activities are weakly planed and implemented. On the other hand Lack of sitting arrangement (41%), Lack of advanced sales ticket (40%), Lack of adequate facilities in stadium are recognized major hindering factors. On the other hand the odd ratio of Gender, eβ = 2.894 (p< .026), Age, eβ = 1.007 (p< .023), Place, eβ = 5.008 (p< .000), Ticketing system, 10.607 (p< .000), and Sitting arrangement 10.619 (p< .000) are identified as strongest predictor of challenging spectator crowd management. In conclusion, stadium safety features and management strategy of these two stadiums are too poor. Up on the end it is recommended that the management of the two stadiums should improve the stadium safety feature and on all Pre, Post and during event management strategies activities used to manage crowds during football matches, especially for derby matches.